Interventions to reduce academic procrastination: A systematic review - Salguero-Pazos, María Rosa; Reyes-de-Cózar, Salvador (International journal of educational research, 2023)
•Procrastination is a phenomenon of great relevance in the literature and related to subjective aspects of students that affect their academic performance.•A review of 72 models of academic procrastination has been used to categorize procrastination.•A gap is found between what is proposed in the literature on procrastination and the aspects being addressed in academic interventions.•The risk of academic procrastination is higher in a social context where the abuse of digital screens increases identity, anxiety, and demotivation. Procrastinating is a common phenomenon that consists of postponing or delaying an activity for later, replacing it with another of lesser importance. This behavior is associated with different variables (psychological, personal and pedagogical) that affect the subject and lead him/her to postpone activities, influencing both academic and well-being levels. In education, this behavior directly affects the teaching-learning processes of students, also affecting their academic performance linked to a failure in the students' self-regulation processes. This research aims to systematize the scientific production on educational interventions aimed at reducing academic procrastination in the classroom. To this end, a systematic review of the literature (PRISMA-P) of the interventions carried out in the last decade (n = 32) was conducted. The results of this study show that, although many variables are worked on in the classroom, self-regulation stands out as the central dimension detailed in the interventions and that there are fundamental aspects, such as personality or anxiety, on which there are fewer studies focused on working on these dimensions. The findings of this study could be helpful to evaluate the potential of existing interventions and serve as a theoretical corpus for the design of future interventions.